THE ROLE OF SOCIAL SUPPORT AND ACADEMIC BUOYANCY ON ACADEMIC BURNOUT IN ORGANIZATIONAL ACTIVIST STUDENTS - Purwanto, Muhammad Dipo Marihdina; Ghozali Rusyid Affandi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of social support and academic buoyancy on academic burnout among university students actively involved in student organizations. Method: A quantitative approach was employed using multiple regression analysis on a sample of 217 male and female students in early adulthood. The participants were selected through proportionate random sampling based on the Isaac & Michael table. Data were collected using three validated instruments: the Burnout Academic Scale (BAS), the Social Support Scale (SCS), and the Academic Buoyancy Scale (ABS). Results: The findings revealed that both social support and academic buoyancy significantly and negatively influenced academic burnout, with a combined contribution of 77.4%. Social support was the more dominant factor, contributing 54.1% to the variance in academic burnout, while academic buoyancy accounted for 23.2%. Novelty: This study highlights the critical role of social support in mitigating academic burnout among student organization members, providing empirical evidence that complements existing literature by emphasizing the interaction between socio-emotional and resilience factors in high-demand academic environments.